The Influence of Family Environment on Student Learning Motivation - Ganeca Larasati Hartoyo; Dian Indriyani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education is not only the responsibility of teachers or educational institutions, but also the responsibility of society, especially the family environment, because before stepping into the wider and more general external environment such as the school and lecture environment, education starts from the smallest community, namely the home. The results of parental education are the first and foremost thing in influencing children's education from childhood until they go to college. The aim of this research is to determine the influence of the family environment on student learning motivation. The method used in this research is quantitative using SPSS 27 software. The conclusion of this research is that there is an influence of the family environment (variable X) on learning motivation (variable Y) in STIA LAN Jakarta Polytechnic students.